LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR OF Atya gbonensis AND Macrobrachium felicinium FROM RIVER BENUE AND RIVER NIGER, NIGERIA - AKISANI, C.A.; ANNUNE, P.A; SOLOMON, S.G. (Nigerian Journal of Fisheries, 2018)
Length-weight parameters (a and b) of the equation: b W  aL were determined for Atya gabonensis and Macrobrachium felicinium caught fortnightly from August 2016 to May 2018 using baskets, fishing net and handpicking in River Benue (Makurdi) and River Niger (Lokoja). Length measurements were made with a plastic ruler while the weight of each specimen was taken using a digital weighing balance. The mean b values were 2.74 and 3.03 for A. gabonensis from Lokoja and Makurdi respectively, showing that A. gabonensis from Makurdi has an isometric growth and A. gabonensis from Lokoja has a negative allometric growth. A. gabonensis from Makurdiwere in better condition than A. gabonensis from Lokoja. The mean b values for M. felicinium from Lokoja and Makurdi were 0.07 and 0.61respectively, showing negative allometric growth for M. felicinium from both Lokoja and Makurdi. M. felicinium from Makurdi were in better condition than M. felicinium from Lokoja. The mean b values for A. gabonensis and M. felicinium were 2.76 and 0.08 respectively, showing that A. gabonensis has a negative allometric growth and M. felicinium negative allometric growth. M.felicinium were in better condition than A. gabonensis.